Project success/failure rates in Turkey - Canser Istanbul Sabahattin Zaim Universitesi; Elif Istanbul Sabahattin Zaim Universitesi (International Journal of Information Systems and Project Management, 2021)

(untitled)
In this study, the success rate of projects in Turkey is measured, and the significant factors behind the successes and the failures of those projects are ranked. To the best of our knowledge, this is the first study widely measuring the success rate of projects in Turkey. The applied methodology is adapted from the Chaos Report by Standish Group. The data for 320 projects with a total budget of approximately $640 million (around 3.6 billion Turkish lira) is collected for the analysis. The results showed that 48% of projects are completed successfully while 45% are eventually completed but either over budget, not on time, or not fully completed. The success rate of the reviewed projects is higher than the rate reported in the Chaos Report. However, the success rate of projects drops to 44% when only technology-driven projects are considered. As the project size increases, the success rate diminishes, as demonstrated in the Chaos Report. The study on the significant factors influencing the success or failure of the projects revealed that the most critical factors are the “requirement definitions”, “requirement planning” and “top management support”.